Cesarean section on a rise—Does advanced maternal age explain the increase? A population register-based study - Rydahl, Eva (PLoS One, 2019)
BACKGROUND: In Denmark, the cesarean section rate has increased by 49% between 1998 and 2015 and accounts for 21% of all births. Cesarean sections may cause short- as well as long-term consequences for both the mother and the child and impose further risks in future pregnancies. Delaying pregnancy until advanced maternal age at childbirth has been suggested as contributing to the increase. The proportion of women giving birth at 35 years or above increased from 15% (1998) to 21% (2015). Advanced maternal age at childbirth has been found to be related to increased pre-pregnancy morbidity and associated risk factors that may contribute to an increased risk of cesarean section. The aim of this study was to examine the association between advanced maternal age and cesarean section in a Danish population and the influence of demographic, anthropometric, health, and obstetric factors on this association. METHODS: This study draws on a national population-based cohort study of all Danish births between 1998 and 2015 (N = 1,122,964). Maternal age less than 30 years serves as reference with the following age categories: (30–34 years); (35–39 years), and (40 years and above). The primary outcome was a cesarean section. Multivariate regression models with adjustment for demographic, health, pregnancy, fetal, and obstetric characteristics were performed with the results further stratified by parity. RESULTS: In general, a positive association between advanced maternal age and cesarean section was found. Only minor changes in the risk estimate occurred after adjustment for relevant confounders. In comparison with the reference category, nulliparous women aged 35-39- years had twice the risk for cesarean section (adjusted odds ratio (AOR) 2.18, 95% confidence interval (CI) [2.11–2.26]) whereas for women of 40 years or above, the risk was more than tripled (AOR 3.64, 95% CI [3.41–3.90]). For multiparous women aged 35-39-years the risk was more moderate, but still with an AOR of 1.56, 95% CI [1.53–1.60], and for those 40 years and above, the AOR was 2.02, 95% CI [1.92–2.09]. CONCLUSIONS: Overall, cesarean section increased with increasing maternal age. Adjustment for maternal and obstetric risk factors had only a minor influence on the association. The association was stronger in nulliparous women compared to multiparous women. Given the lack of impact of demographic and health risks on the relationship between maternal age and cesarean section, the authors suggest obstetric culture could be added to the list of risk factors for a cesarean. Future research on obstetric culture is recommended as are studies on a possible age-related decrease in the ability to maintain the progression of labor. TRIAL REGISTRATION: The study uses depersonalized register data and has been approved by the Danish Data Protection Agency (2015-41-4168).